Association and epistatic analysis of white matter related genes across the continuum schizophrenia and autism spectrum disorders: The joint effect of NRG1-ErbB genes. (16th March 2022) - Prats, C.; Fatjó-Vilas, M.; Penzol, M. J.; Kebir, O.; Pina-Camacho, L.; Demontis, D.; Crespo-Facorro, B.; Peralta, V.; González-Pinto, A.; Pomarol-Clotet, E.; Papiol, S.; Parellada, M.; et al.
Abstract: Background: Schizophrenia-spectrum disorders (SSD) and Autism spectrum disorders (ASD) are neurodevelopmental disorders that share clinical, cognitive, and genetic characteristics, as well as particular white matter (WM) abnormalities. In this study, we aimed to investigate the role of a set of oligodendrocyte/myelin-related (OMR) genes and their epistatic effect on the risk for SSD and ASD. Methods: We examined 108 SNPs in a set of 22 OMR genes in 1749 subjects divided into three independent samples (187 SSD trios, 915 SSD cases/control, and 91 ASD trios). Genetic association and gene-gene interaction analyses were conducted with PLINK and MB-MDR, and permutation procedures were implemented in both. Results: Some OMR genes showed an association trend with SSD, while after correction, the ones that remained significantly associated were MBP, ERBB3, and AKT1. Significant gene-gene interactions were found between (i) NRG1 * MBP ( perm p -value = 0.002) in the SSD trios sample, (ii) ERBB3*AKT1 ( perm p -value = 0.001) in the SSD case-control sample, and (iii) ERBB3 * QKI ( perm p -value = 0.0006) in the ASD trios sample. Discussion: Our results suggest the implication of OMR genes in the risk for both SSD and ASD and highlight the role of NRG1 and ERBB genes. These findings are in line with the previous evidence and may suggest pathophysiological mechanisms related to NRG1/ERBBs signalling in these disorders.